Preparation method of pure-phase Fe5C2 nano material
By using ferrous ferric ferric ferricyanide as the precursor in a reducing atmosphere, the problem of excessive phases of iron carbide products in traditional methods is solved, and the preparation of pure phase Fe5C2 nanomaterials is realized, suitable for mass production and has broad application prospects.
Patent Information
- Application Number
- CN202510722754.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-15
AI Technical Summary
Traditional methods have many heterogeneous phases and complex processes for synthesis of iron carbide products, making it difficult to prepare high-purity Fe5C2, which hinders the precise regulation of the active phase structure and in-depth analysis of the reaction mechanism.
Ferrous ferrocyanide is used as the precursor and carbonized calcination is carried out in a reducing atmosphere to prepare a pure phase Fe5C2 nanomaterial. By controlling the reaction conditions and atmosphere composition, the purity and uniformity of the product are ensured.
It realizes a simple and safe preparation process of Fe5C2 nanomaterials, and the products are pure, suitable for mass production, and has broad application prospects.
Smart Images

Figure CN120483157A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano material preparation, and particularly relates to a method for preparing pure phase Fe5C2 nano material. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Fischer-Tropsch Synthesis (FTS) and carbon dioxide hydrogenation reactions can directly convert carbon sources such as CO and CO2 into high-value-added hydrocarbon fuels and chemicals. Iron-based catalysts have become a research hotspot in this field due to their advantages such as low cost, high activity, and strong adaptability. However, iron oxides (such as Fe2O3) themselves have low catalytic activity and need to be activated in a reducing atmosphere (such as H2 / CO) and undergo carburization reaction to form iron carbide (Fe x C y ) and other active phases to exhibit excellent catalytic performance.
[0004] Research has shown that iron carbide, particularly Fe5C2, is the key active phase in the Fischer-Tropsch reaction. However, traditional iron carbide synthesis methods (such as wet chemical methods, vapor-phase carbonization, and laser pyrolysis) often face challenges such as harsh reaction conditions, high energy consumption, and the presence of multiple product phases (e.g., the coexistence of Fe3C, Fe2C, Fe5C2, and Fe7C3). This not only complicates catalyst optimization but also hinders precise control of the active phase structure and in-depth elucidation of the reaction mechanism. Therefore, developing an efficient, low-cost, and controllable method for the preparation of single-phase Fe5C2 is crucial for improving catalyst performance, better understanding the distribution and evolution of the active phase, and optimizing the design of iron carbide catalysts. In recent years, precursors such as Prussian blue analogs (PBAs) have demonstrated unique advantages in nanomaterial synthesis due to their tunable structure and uniform elemental distribution. Teng's blue (ferrous ferrocyanide, Fe3[Fe(CN)6]2), a typical Prussian blue-like compound, possesses a rich Fe-CN coordination structure, providing a uniform carbon and iron source during pyrolysis, promising the precise synthesis of Fe5C2. However, the preparation of high-purity Fe5C2 using Teng's blue has yet to be reported.
[0005] Based on this, there is an urgent need to develop a simple and controllable Fe5C2 synthesis strategy to solve the problems of multiple product phases and complex processes in traditional methods, and to provide new ideas for the design of high-performance iron-based catalysts. Summary of the Invention
[0006] In response to the shortcomings of the prior art, the present invention provides a method for preparing pure Fe5C2 nanomaterials. The method is simple, employs mild conditions, and produces a pure product. Using ferrous ferrocyanide as a precursor, pure Fe5C2 is prepared by carbonization in a reducing atmosphere. The method is suitable for preparing Fe5C2 powder materials for mass production.
[0007] In order to achieve the above object, the technical solution of the present invention is: A method for preparing a pure phase Fe5C2 nanomaterial comprises the following steps: S1. Weigh a certain amount of ferrous salt and potassium ferrocyanide, dissolve them in deionized water to prepare a first solution and a second solution, and stir to fully dissolve them.
[0008] S2. Under stirring conditions, add the prepared first solution to the second solution at a uniform speed, and continue stirring for a period of time after the operation is completed.
[0009] S3. The mixed solution is allowed to stand and age at room temperature, and then centrifuged, washed, dried, and ground to obtain ferrous ferrocyanide (Fe3[Fe(CN)6]2).
[0010] S4. Carbonizing and calcining the ground ferrous ferrocyanide in a reducing atmosphere, and taking it out after carbonization to obtain a pure phase nano-iron carbide material.
[0011] In one or more embodiments, in step S1, based on water solubility and stability, the ferrous salt is one or more of ferrous chloride, ferrous acetate, and ferrous sulfate.
[0012] In one or more embodiments, in step S1, the concentration of the solute in the first solution and the second solution is 0.5 mmol / L to 100 mmol / L.
[0013] In one or more embodiments, in step S1, an appropriate amount of polyvinylpyrrolidone (PVP) may be added to the potassium ferrocyanide solution, with the amount of polyvinylpyrrolidone added being 0 to 40 g / L. PVP is a polymeric surfactant that can adsorb onto the surface of ferrous ferrocyanide particles through its polar groups, forming steric hindrance. This slows nucleation during the reaction, facilitates the formation of uniformly sized crystals, and produces evenly dispersed nanoparticles.
[0014] In one or more embodiments, in step S2, the solute molar ratio of the first solution to the second solution (ferrous source: potassium ferrocyanide) is 0.3-3:1, preferably 3:2.
[0015] In one or more embodiments, in step S2, the uniform addition process is preferably slow dropwise addition at a rate of 0.2-3 mL / min. Stirring is continued for 5 to 240 minutes after the addition is completed, preferably for 10 to 30 minutes. Uniform addition, especially slow dropwise addition of the second solution accompanied by stirring, can improve mixing of the first and second solutions, enhance mass transfer, and ensure a more complete reaction, thereby facilitating the production of particles of uniform size.
[0016] In one or more embodiments, in step S3, the standing time at room temperature is 5 to 96 hours, preferably, the standing time is 24 to 48 hours.
[0017] In one or more embodiments, in step S3, the cleaning reagents used are deionized water and anhydrous ethanol. Preferably, the product is first cleaned twice with deionized water and then cleaned twice or more with anhydrous ethanol. The water and anhydrous ethanol cleaning are used to remove soluble impurities attached to the product.
[0018] In one or more embodiments, in step S3, the drying temperature is 60-100° C., and the drying time is 12-48 h.
[0019] In one or more embodiments, in step S4, the reducing atmosphere is a mixture of H2 / CO2, H2 / CO2 / N2, or H2 / CO2 / Ar, wherein the H2:CO2 feed ratio is 0.5-8:1, and the H2:CO2 feed ratio can be any ratio in the range of 0.5-8:1, such as 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, etc. Preferably, the H2:CO2 feed ratio is 3:1. An appropriate H2 / CO2 ratio can suppress oxidation of the precursor while utilizing CO2 cracking to provide a carbon source for deep carbonization, whereas the target product cannot be obtained in an oxidizing atmosphere such as CO2 or an inert gas such as N2.
[0020] In one or more embodiments, in step S4, the heating rate is 2-10°C / min; the reduction temperature is 270-400°C. Too low a temperature will result in incomplete transformation of the precursor; the calcination time is 3-20 h; and the CO2 gas flow rate is 3-200 mL / min. The beneficial effects of the present invention are: The present invention proposes a new method for preparing Fe5C2 powder nanomaterials. Compared with traditional preparation methods, the present invention uses cheap and easily available ferrous ferrocyanide as a precursor and calcines the catalyst in one step. The preparation conditions are simple, the process is safe, the carbonization reaction time is greatly reduced, and the product is a pure single-phase nanomaterial, which is suitable for mass production and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings, which constitute part of the present invention, are intended to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are intended to explain the present invention and do not constitute undue limitations thereon. It is obvious that one of ordinary skill in the art could derive other drawings based on these drawings without inventive effort.
[0022] Figure 1 These are the X-ray diffraction (XRD) pattern and transmission electron microscopy (TEM) pattern of Fe5C2 obtained in Example 1 of the present invention, wherein (a) is the XRD pattern of Fe5C2, and (b) is the TEM pattern of Fe5C2.
[0023] Figure 2 These are the XRD patterns and TEM patterns of Fe5C2 obtained in Example 2 of the present invention, wherein (a) is the XRD pattern of Fe5C2, and (b) is the TEM pattern of Fe5C2.
[0024] Figure 3 These are the XRD patterns and TEM patterns of Fe5C2 obtained in Example 3 of the present invention, wherein (a) is the XRD pattern of Fe5C2, and (b) is the TEM pattern of Fe5C2.
[0025] Figure 4 It is the XRD pattern of the material obtained in Comparative Example 1 of the present invention.
[0026] Figure 5 This is the XRD pattern of the material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0027] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs.
[0028] The technical solution of the present invention is further described below with reference to specific examples. The present invention has no particular limitation on the sources of the reagents used in the following examples, and commercially available products known to those skilled in the art can be used.
[0029] Example 1: Weigh 0.75 mmol of ferrous sulfate and prepare a solution in 100 mL of deionized water. Weigh 0.5 mmol of potassium ferrocyanide and 2 g of PVP and add them to 100 mL of deionized water to prepare a solution. Stir to fully dissolve. Add the prepared ferrous sulfate solution dropwise to the potassium ferrocyanide solution at a rate of 1 mL / min and continue stirring for 20 minutes. The mixed solution is allowed to stand at room temperature for 24 hours. The resulting ferrous ferrocyanide is centrifuged, washed twice with deionized water and then twice with anhydrous ethanol, dried at 60°C for 24 hours, and then ground. The ground ferrous ferrocyanide is placed in a mixed atmosphere of H2:CO2:N2 (a feed ratio of 3:1:1) with a CO2 gas flow rate of 3 mL / min. Carbonization and calcination are performed at 330°C for 13 hours. After carbonization, the product is removed and calcined to obtain Fe5C2.
[0030] See also Figure 1 ,from Figure 1 As can be seen in (a), the peak position of the material coincides with the main peak position of the Fe5C2 standard card, indicating that the iron carbide obtained is pure phase Fe5C2. The morphology of the nanomaterial is as follows Figure 1 (b) shows particles of about 10-30 nm.
[0031] Example 2: Weigh 0.6 mmol of ferrous sulfate and prepare a solution in 20 mL of deionized water. Weigh 0.4 mmol of potassium ferrocyanide and prepare a solution in 20 mL of deionized water, stirring to fully dissolve. Add the prepared ferrous sulfate solution dropwise to the potassium ferrocyanide solution at a rate of 1 mL / min, stirring continuously for 10 minutes. The mixed solution is allowed to stand at room temperature for 24 hours. The resulting ferrous ferrocyanide is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, dried at 60°C for 24 hours, and then ground. The ground ferrous ferrocyanide is placed in a mixed atmosphere of H2:CO2 (a 4:1 ratio) with a CO2 flow rate of 4 mL / min and carbonized at 330°C for 10 hours. After carbonization, it is removed to yield Fe5C2.
[0032] See also Figure 2 ,from Figure 2 As can be seen in (a), the peak position of the material coincides with the main peak position of the Fe5C2 standard card, indicating that the iron carbide obtained is pure phase Fe5C2. The morphology of the nanomaterial is as follows Figure 2 (b) shows particles of about 10-80 nm.
[0033] Example 3: Weigh 0.6 mmol of ferrous sulfate and prepare a solution in 20 mL of deionized water. Weigh 0.4 mmol of potassium ferrocyanide and 1 g of PVP and add them to 20 mL of deionized water to prepare a solution, stirring until fully dissolved. The prepared ferrous sulfate solution was added dropwise to the potassium ferrocyanide solution at a rate of 3 mL / min, and stirring continued for 30 minutes. The mixed solution was allowed to stand at room temperature for 24 hours. The resulting ferrous ferrocyanide was centrifuged, washed twice with deionized water and twice with anhydrous ethanol, dried at 60°C for 24 hours, and then ground. The ground ferrous ferrocyanide was placed in a mixed atmosphere of H2:CO2:N2 (a feed ratio of 3:1:4) with a CO2 gas flow rate of 10 mL / min. Carbonization and calcination were performed at 350°C for 12 hours. After carbonization, the product was removed and obtained as Fe5C2.
[0034] See also Figure 3 ,from Figure 3 As can be seen in (a), the peak position of the material coincides with the main peak position of the Fe5C2 standard card, indicating that the iron carbide obtained is pure phase Fe5C2. The morphology of the nanomaterial is as follows Figure 3 (b) shows particles of about 10-30 nm.
[0035] Comparative Example 1: Weigh 0.6 mmol of ferrous sulfate and prepare a solution in 20 mL of deionized water. Weigh 0.4 mmol of potassium ferrocyanide and 1 g of PVP and add them to 20 mL of deionized water to prepare a solution. Stir to fully dissolve. Pour the prepared ferrous sulfate solution directly into the potassium ferrocyanide solution and continue stirring for 30 minutes. The mixed solution is allowed to stand at room temperature for 24 hours. The resulting ferrous ferrocyanide is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, dried at 60°C for 24 hours, and then ground. The ground ferrous ferrocyanide is placed in a mixed atmosphere of a CO2:N2 feed ratio of 1:4 with a CO2 gas flow rate of 15 mL / min. Carbonization and calcination are performed at 350°C for 12 hours. After the reaction is complete, the ferrous ferrocyanide is removed to obtain a black powder.
[0036] See also Figure 4 ,from Figure 4 It can be seen that the peak position of the XRD pattern of the material coincides with the main peak position of the Fe3O4 standard card, indicating that iron carbide cannot be produced under this condition.
[0037] Comparative Example 2: Weigh 0.6 mmol of ferrous sulfate and prepare a solution with 20 mL of deionized water. Weigh 0.4 mmol of potassium ferrocyanide and 1 g of PVP and add them to 20 mL of deionized water to prepare a solution. Stir to fully dissolve. Pour the prepared ferrous sulfate solution directly into the potassium ferrocyanide solution and continue stirring for 30 minutes. The mixed solution is allowed to stand at room temperature for 24 hours. The resulting ferrous ferrocyanide is centrifuged, washed twice with deionized water and twice with anhydrous ethanol, dried at 60°C for 24 hours, and then ground. The ground ferrous ferrocyanide is placed in a nitrogen atmosphere with a gas flow rate of 80 mL / min and carbonized and calcined at 350°C for 12 hours. After the reaction is complete, remove the mixture to obtain a black powder.
[0038] See also Figure 5 ,from Figure 5 It can be seen that the peak position of the XRD pattern of the material coincides with the main peak position of the Fe2N standard card, indicating that iron carbide cannot be obtained under this condition.
[0039] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.
Claims
1. A method for preparing pure phase Fe5C2 nanomaterials, characterized in that: The following steps are involved: S1. Weigh a certain amount of ferrous salt and potassium ferrocyanide, dissolve them in deionized water to prepare a first solution and a second solution, and stir to fully dissolve them; S2. Under stirring conditions, the prepared first solution is added to the second solution at a uniform rate, and stirring is continued for a period of time after the operation is completed; S3, allowing the mixed solution to stand for aging at room temperature, centrifuging, washing, drying, and grinding to obtain ferrous ferrocyanide; S4, carbonizing and calcining the ground ferrous ferrocyanide in a reducing atmosphere, and taking it out after carbonization to obtain a pure phase nano-iron carbide material; Wherein, the reducing atmosphere is one of H2 / CO2, H2 / CO2 / N2, and H2 / CO2 / Ar mixed gases.
2. The method according to claim 1, characterized in that In step S1, the ferrous salt is one or more of ferrous chloride, ferrous acetate, and ferrous sulfate.
3. The method according to claim 1, characterized in that In step S1, the concentration of the solute in the first solution and the second solution is 0.5 mmol / L to 100 mmol / L.
4. The method according to claim 1, wherein In step S1, an appropriate amount of polyvinyl pyrrolidone may be added to the potassium ferrocyanide solution, and the amount of polyvinyl pyrrolidone added is 0-40 g / L.
5. The method according to claim 1, wherein In step S2, the solute molar ratio of the first solution to the second solution is 0.3-3:
1.
6. The method according to claim 1, characterized in that In step S2, the uniform addition process is preferably performed dropwise and slowly, and the stirring time after the addition is completed is 5 to 240 minutes.
7. The method according to claim 1, characterized in that In step S3, the standing time at room temperature is 5 to 96 hours.
8. The method according to claim 1, characterized in that In step S3, the cleaning reagents used are deionized water and anhydrous ethanol. The specific operation is to first clean with deionized water twice, and then clean with anhydrous ethanol twice or more.
9. The method according to claim 1, characterized in that In step S4, the reducing atmosphere is one of H2 / CO2, H2 / CO2 / N2, and H2 / CO2 / Ar mixed gases, and the H2:CO2 feed ratio is 0.5-8:
1.
10. The method according to claim 1, characterized in that In step S4, the heating rate is 2-10°C / min; the reduction temperature is 270-400°C; the calcination time is 3-20 h; and the CO2 gas flow rate is 3-200 mL / min.